Pseudomonasdiarrhea in a child suffering from acute lymphatic leukemia - De, A; Mathurkar, H; Baveja, S; Manglani, M V (Indian Journal of Medical and Paediatric Oncology, 2009)
A female child admitted to hospital, diagnosed with acute lymphatic leukemia - CALLA positive, developed loose motions. Her stool culture and blood culture grew Pseudomonas aeruginosa. Although the diarrhea subsided after five days, the stool culture repeatedly grew P. aeruginosa for more than one month, in spite of treatment. Even though diarrhea due to Pseudomonas is rare, it can yet be seen in immunocompromised patients and is also associated with neutropenic enterocolitis. Stool specimens of all leukemia patients on chemotherapy and suffering from diarrhea, should be sent routinely for culture, so as to find out the exact cause of the diarrhea. Proper reporting will enable the clinicians to start appropriate antibiotics, thereby, reducing the morbidity and mortality of the leukemia patients.
Keywords: Acute lymphatic leukemia; Pseudomonas; diarrhea